State-of-the-art methods for detecting organochlorine pesticides in fruits (@limentech, Ciencia y Tecnología Alimentaria, 2016)
The study of pesticide residues in food has been a constant research endeavor, and analytical monitoring is becoming increasingly important, becoming more standardized, and requiring in-situ and real-time monitoring techniques. Biosensors, for example, are a highly precise and accurate tool for monitoring systems. Therefore, this review aims to highlight some developments in sample treatment and instrumental complements for optimizing the identification and quantification of contaminants in food matrices. To this end, the techniques used, extraction methods, and innovative alternative trends for the analysis of these compounds are listed. Finally, the research conducted on this topic in the food sector and the advances that have been developed to improve analytical techniques are included.
Keywords: Fruits; extraction methods; pesticides; multisensory system